1984
DOI: 10.1063/1.332937
|View full text |Cite
|
Sign up to set email alerts
|

Hole traps and trivalent silicon centers in metal/oxide/silicon devices

Abstract: Interaction of molecular hydrogen with trapped hole E' centers in irradiated and high field stressed metal/oxide/silicon oxides Dependence of radiationinduced interface traps on gate Al thickness in metal/SiO2/Si structures We report electron spin resonance (ESR) measurements of E' -center (a "trivalent silicon" center in SiOz) density as well as capacitance versus voltage (C-V) measurements on y-irradiated metal! oxide/silicon (MOS) structures. We also report a considerable refinement of earlier ESR measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
191
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(207 citation statements)
references
References 43 publications
12
191
1
Order By: Relevance
“…The total defect concentration is N T = 2.05 Â 10 12 cm À2 . These results are consistent with the considerations and quasi-static measurements [32,34].…”
Section: Impedance Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…The total defect concentration is N T = 2.05 Â 10 12 cm À2 . These results are consistent with the considerations and quasi-static measurements [32,34].…”
Section: Impedance Analysissupporting
confidence: 82%
“….Þ have been taken from measurement values based on scanning tunneling spectroscopy studies for single-defect Si dangling bonds [25]. The dynamics of other oxide traps (E c and E d [7,32]) are better described including metastable states [11,24]. However, EPR studies indicated that these defects relax almost immediately after the removal of the stress condition [9], and thus they have not been investigated in this study.…”
Section: Model Description and Validationmentioning
confidence: 99%
“…This is not very likely, since it has been established that the majority of the radiation-induced oxide-trap charge is from holes trapped at EЈ centers. 13 The data in Fig. 1 are in accordance with the so-called hydrogen cracking models, 1,4,5 as they assume as a first step diffusion to the Si/SiO 2 interface of radiolytic H 2 released in the gate oxide and/or adjacent structures ͑poly-Si gate, chemical-vapor-deposited oxide͒.…”
Section: ͓S0003-6951͑01͒02601-8͔supporting
confidence: 52%
“…It is well known that ionizing radiation generally degrades the performance of Si microelectronic devices by creating interface traps and oxide-trapped charge [11,10]. The interface traps consist of Si atoms at the interface that failed to bond to the oxide [12]. Such traps act as recombination centers for electrons and holes, and this recombination leads to increased base current in bipolar transistors [10].…”
Section: Project Description and Discussionmentioning
confidence: 99%